Gas6 induces AIM to suppress acute lung injury in mice by inhibiting NLRP3 inflammasome activation and inducing autophagy - Jeong, Seonghee; Yang, Kyungwon; Lee, Ye‐Ji; Park, Joo-Won; Park, Eun-Mi; Kang, Jihee Lee (Frontiers in Immunology, 2025)
IntroductionGrowth arrest-specific 6 (Gas6) protein signaling plays a critical role in maintaining immune homeostasis and regulating inflammation. However, novel mechanisms for modulating macrophage activity through the Gas6 axis are being identified. Gas6 enhances the production of apoptosis inhibitor of macrophages (AIM), a protein with potent anti-inflammatory properties. This study investigates whether Gas6-induced AIM suppresses acute lung injury (ALI) in mice by modulating key inflammatory pathways, including inflammasome activation, autophagy, reactive oxygen species (ROS) generation, and efferocytosis.MethodsALI was induced in wild-type (WT) and AIM−/− mice via intratracheal administration of LPS. To evaluate the effects of the Gas6-AIM axis on lung inflammation, recombinant Gas6 (rGas6) was treated intraperitoneally. Inflammatory responses were evaluated using enzyme-linked immunosorbent assay, a cell-sizing analyzer, and Bicinchoninic acid assays. Lung pathology was assessed using hematoxylin-eosin staining. NLRP3 inflammasome activation and autophagy were evaluated using western blot, quantitative real-time PCR, and immunofluorescence. Reactive oxygen species (ROS) levels in alveolar macrophages were measured via fluorescence microscopy, while efferocytosis was assessed in cytospin-stained BAL cells and cultured alveolar macrophages co-cultured with apoptotic Jurkat cells. Additionally, rGas6-mediated effects on NLRP3 inflammasome activation and autophagy were validated in mouse bone marrow-derived macrophages (BMDMs) using siRNAs targeting AIM, Axl, LXRα, or LXRβ.ResultsProinflammatory cytokine production, neutrophil infiltration, and protein levels in BALF were significantly reduced by rGas6 administration in WT mice but not in AIM−/− mice. Specifically, rGas6 reduced IL-1β and IL-18 levels, caspase-1 activity, and the production of apoptosis-associated speck-like protein containing a caspase activation and recruitment domain (ASC) in alveolar macrophages. Additionally, rGas6 promoted autophagy and efferocytosis in alveolar macrophages while reducing ROS levels through AIM production. These protective effects were absent in AIM−/− mice. Furthermore, siRNA-mediated silencing of Axl, LXRα, LXRβ, or AIM reversed the inhibitory effects of rGas6 on NLRP3 inflammasome activation in BMDMs, and AIM was essential for rGas6-induced autophagy.ConclusionGas6-induced AIM production protects against LPS-induced ALI by inhibiting NLRP3 inflammasome activation, enhancing autophagy and efferocytosis, and reducing oxidative stress. These findings highlight the Gas6–AIM axis as a potential therapeutic target for mitigating inflammatory lung diseases.